MORPHOMETRY OF FETAL PLACENTA AND ITS ASSOCIATION WITH CALF AND DAM IN ONGOLE (BOS INDICUS) COWS - Shaik Yasmeen; M. Mutha Rao; Makkena Sreenu; N.R. Srikanth; K. Sunny Praveen (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Placenta plays a vital role in the exchange of nutrients between the dam and fetus, ensures fetal growth and survival. Its structural and functional characteristics significantly affect the health and productivity of both calf and dam. The present study was conducted to assess the morphological characteristics of normally expelled foetal placenta and it’s association with various calf and dam parameters in the native Ongole (Bos indicus) cows. The objectives of the present study aimed to assess the morphological characteristics of foetal placenta expelled normally in Ongole cows and examine their association with various calf and dam parameters. It also evaluated the influence of factors such as calf sex, dam weight, parity and season on placental traits and expulsion duration. The study was conducted at the Livestock Research Station, Lam, Guntur, A.P, and a total of 123 placentas from normally calved animals were used. The mean values for duration of placenta expulsion, weight of placenta, number of cotyledons, overall cotyledon diameter, placental efficiency and placenta density were recorded to be 203 ± 6.5 minutes, 3.18 ± 0.06, 77.03 ± 1.32, 6.16 ± 0.06 cm, 8.38 ± 0.17 and 0.03 ± 0.004 respectively.  73.98% of placenta expelled ≥ 4hrs. The placenta weight was found to be 0.84% of dam’s weight and 12.51% of calf birth weight. The number of cotyledons differed significantly (P